A Description of the Artistic Image of the Works of Guy de Mopassan and Abdullah Qadiri - Jabbarova Malohat Hamdamovna (Indonesian Journal of Innovation Studies, 2022)
The article provides an overview of the artistic analysis of the works of Guy de Mopassan and Abdullah Qadiri. At the same time, the works of the creatorswere analyzed using comprehensive examples. There is also a discussion of the artisticmeans used in the works.